Aging Immunity Microbiome Axis - Shnawa, Ibrahim M S (British Journal of Healthcare and Medical Research, 2026)
Human ageing influence immunity and modify microbiome. Ageing scientific workers have made three questions as; why ageing, why do we age, and how do we age. They evolve theories in trying to answer them. The concepts of; ageing, immunity and microbiome were elucidated. Ageing affect immunity , ageing affect microbiome. Mutual communications between these elements were bidirectional. The objective of the present opinion paper was to suggest and prove for an” Ageing-immunity-microbiome axis” through review current relevant publications and showcase analysis for an age human population. This suggested axis pathway starts as low grade inflammation, chronic low grade inflammation, inflamm-ageing , inflamma-immuno-ageing, immune senescence then microbiome modifications. Each of the tripartite elements of the axis affect and affected by the other via multiple bidirectional cross-talk communications.